Solasonine Causes Redox Imbalance and Mitochondrial Oxidative Stress of Ferroptosis in Lung Adenocarcinoma - Zeng, Yao-Ying; Luo, Ying-Bin; Ju, Xu-Dong; Zhang, Bo; Cui, Ya-Jing; Pan, Yan-Bin; Tian, Jian-Hui; Teng, Wen-Jing; Wu, Jianchun; Li, Yan (Frontiers in Oncology, 2022)
Ferroptosis, an iron-dependent form of oxidative cell death driven by excessive lipid peroxidation, is emerging as a promising cancer therapeutic approach. Solasonine is reported as a potential compound in tumor suppression of which intimately attribute to ferroptosis. However, the knowledge of ferroptosis induced by solasonine is inadequately identifies and elaborates in lung adenocarcinoma, a fatal disease with high morbidity and mortality rates. First of all, the biochemical and morphological changes of Calu-1 and A549 cells exposed to solasonine were observed through cell death assay and microscope. After determining the executive concentration of solasonine, the cell viability assay was conducted to measure the effects of solasonine on tumor growth of Calu-1 and A549 cells. Then, the ferroptosis was identified through CCK-8, lipid peroxidation assessment, Fe2+ and ROS detection, with the assist of application of available ferroptosis-related reagents. Further, to distinct the potential pathways, the antioxidant system contains GSH, Cys, GPx4, SLC7A11 and mitochondrial dysfunction were measured. The results were solasonine exactly exerted the ability of against lung adenocarcinoma cells. Ferroptosis contributed to the solasonine-induced cell death accompany with accumulation of lipid peroxide, Fe2+ and ROS. Additionally, the collapses of antioxidant defense and damage in mitochondria were considered assuming major responsibility in ferroptosis occurrence triggered by solasonine. Collectively, the study described the potential process of ferroptosis induced by solasonine when deal with lung adenocarcinoma. This favorable data support that solasonine serves as a prospective compound in lung cancer intervention.